Respostas

A melhor resposta!
2014-08-05T15:51:50-03:00
(E) 10x + 1 = 4 - 5
10x = 4 - 5 - 1
10x = - 2
x = - 2 / 10
x = -0,20

(F) x + 15 = 11
x = 11 - 15
x = - 4 

(G) 5x + 3x = 16
8x = 16
x = 16 / 8
x = 2
1 5 1
(H) x+x+8 =54 (i) 7x-2-5x =18 (J) -x-2x-4 =11 (K) 4(x+1)=12
(H) x + 8 = 54
x = 54 - 8
x = 46

(I) 7x - 2 - 5x = 18
7x - 5x = 18 + 2
2x = 20
x = 20 / 2
x = 10

(J) -x - 2x - 4 = 11
-3x = 11 + 4
-3x = 15
x = 15 / -3
x = -5

(K) 4 (x + 1) = 12
4x + 4 = 12
4x = 12 - 4
4x = 8
x = 8 / 4
x = 2
(L) 9x-3(2x+2)=15 (M) 6(3x+2)-8= -2 (N) -3(x-5)-2(2x+1)= -8 (O) 2(x+1)+10=38
2014-08-05T16:21:35-03:00
E) 10x+1-4-5=0⇒10x=-8⇒x=8/10⇒x=0,8  F)x+15=11⇒x=11-15⇒x=-4
G)5x+3x=16⇒8x=16⇒x=16/8⇒x=2
1 5 1
(L) 9x-3(2x+2)=15 (M) 6(3x+2)-8= -2 (N) -3(x-5)-2(2x+1)= -8 (O) 2(x+1)+10=38